(untitled) (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2024)
This research aims to determine the effectiveness of the shadowing technique on students’ speaking skills among the tenth-grade students of SMA YPK Pematangsiantar. This research was classified as a quasi-experimental. It uses two groups, class X IPS 3 as the experimental group and class X MIPA 1 as the control group. The experimental group was students who taught by using the shadowing technique whereas the control group was students who taught without using the shadowing technique. The sample of this research was 28 students of the experimental group and 28 students of the control group. The data were obtained using the pre-test and post-test that was given to both groups. The data of the pre-test and the post-test of both groups were analyzed by using SPSS 26 forms. Based on the data analysis, the researcher found that the students taught speaking using the shadowing technique will show better achievement than those taught without using the shadowing technique. From the result of the computation, in which the value t-test is higher than t-table (2.050 > 1.703). Therefore, Ha was accepted and H0 was rejected. From the description above, it can be concluded that the shadowing technique is effective on students’ speaking skills at the tenth-grade students of SMA YPK Pematangsiantar. After conducting this study, the researcher can give some suggestions to students to be more creative and motivated to practice speaking skills, improve vocabulary and grammar, and continue to work hard to be able to speak English well and correctly. Teachers are advised to provide varied teaching methods, prepare materials and students well, organize time effectively, and encourage more speaking practice. Overall, the shadowing technique is a valuable tool for improving English speaking